Viva La Ova - The Journey!/Jamiyah Hassan - Hassan, Jamiyah (University Of Malaya, 2015)
The journey of a woman from the womb to the tomb starts with the little ova. The challenges of pregnancy and its potential complications can convert a naturally physiological event to something more deadly. A woman who dies during pregnancy and delivery is a tragedy that we want to avoid. For over five decades Malaysia has improved the obstetric services and maternal mortality has reduced significantly. Family planning and effective contraception will be the much needed strategy to achieve maternal mortality comparable to the more developed world.